Principles and practice of constraint programming : 23rd International Conference, CP 2017, Melbourne, VIC, Australia, August 28-September 1, 2017, Proceedings /: 23rd International Conference, CP 2017, Melbourne, VIC, Australia, August 28-September 1, 2017, Proceedings. (2017) - Unknown
No abstract available